Monitoring the biomechanics of a wheelchair sprinter racing the 100m final at the 2016 Paralympic Games - Barbosa, Tiago M. (2017)
The aim was to run a case study of the biomechanics of a wheelchair sprinter racing the 100 m final at the 2016 Paralympic Games. Stroke kinematics was measured by video analysis in each 20 m split. Race kinetics was estimated by employing an analytical model that encompasses the computation of the rolling friction, drag, energy output and energy input. A maximal average speed of 6.97 m s(-1) was reached in the last split. It was estimated that the contributions of the rolling friction and drag force would account for 54% and 46% of the total resistance at maximal speed, respectively. Energy input and output increased over the event. However, we failed to note a steady state or any impairment of the energy input and output in the last few metres of the race. Data suggest that the 100 m is too short an event for the sprinter to be able to achieve his maximal power in such a distance.